(2х+8)-(5+х)=6 (3а-4)+(2а-7)=4 9х-6=(5х+8)-(5х-12) решить уравнение Помогите пожалуйста

0 голосов
32 просмотров

(2х+8)-(5+х)=6 (3а-4)+(2а-7)=4 9х-6=(5х+8)-(5х-12) решить уравнение Помогите пожалуйста


Математика (16 баллов) | 32 просмотров
Дан 1 ответ
0 голосов

Уравнение 1.

(2х+8)-(5+х)=6

2х+8-5-х=6

х=3

Ответ: 3.

Уравнение 2.

(3а-4)+(2а-7)=4

3а-4+2а-7=4

5а=15

а=3

Ответ: 3.

Уравнение 3.

9х-6=(5х+8)-(5х-12)

9х-6=5х+8-5х+12

9х=26

х=26/9

х=3 1/9

Ответ: 3 1/9.

(5.8k баллов)
0

я исправила, обрати внимание))

0

а то вдруг)